Patents and the experimental space: social, legal and geographical dimensions of 3D bioprinting. Issue 1 (2nd January 2021) - Bicudo, Edison; Faulkner, Alex; Li, Phoebe
ABSTRACT: The entanglements between social creativity, legal instruments and global policies become particularly clear in emerging technological fields where such relations are being established or improvised. In this paper, an analysis of such entanglements is delivered, focusing on 3D bioprinting. This technique amounts to the use of robotic, computer-controlled devices called bioprinters, with which bioactive structures are manufactured, with potential medical applications. Bioprinting has triggered manifold relations and processes here grasped with the concept of experimental space. It is claimed that the experimental space has several dimensions, three of which are analysed here. First, there is a legal dimension formed by the multiplication of patent documents making reference to each other and forming a discursive network. Second, there is a social dimension, as the experimental space is populated by innovative companies and universities involved with bioprinting. Finally, the geographical dimension derives from the spatial processes and global geography of bioprinting. The study of these three dimensions is underpinned by a quantitative analysis of bioprinting patents filed from 2001 to 2019 and found on two specialized websites (The Lens and Google Patents). Furthermore, fieldwork was conducted in three countries (the UK, Brazil, and Italy), involving interviews with academics and entrepreneurs exploring bioprinting.